Dietary Inulin Increases Lactiplantibacillus plantarum Strain Lp900 Persistence in Rats Depending on the Dietary-Calcium Level - Fuhren, Jori (Appl Environ Microbiol, 2021)
Synbiotics are food supplements that combine probiotics and prebiotics to synergistically elicit health benefits in the consumer. Lactiplantibacillus plantarum strains display high survival during transit through the mammalian gastrointestinal tract and were shown to have health-promoting properties. Growth on the fructose polysaccharide inulin is relatively uncommon in L. plantarum, and in this study we describe FosE, a plasmid-encoded β-fructosidase of L. plantarum strain Lp900 which has inulin-hydrolyzing properties. FosE contains an LPxTG-like motif involved in sortase-dependent cell wall anchoring but is also (partially) released in the culture supernatant. In addition, we examined the effect of diet supplementation with inulin on the intestinal persistence of Lp900 in adult male Wistar rats in diets with distinct calcium levels. Inulin supplementation in high-dietary-calcium diets significantly increased the intestinal persistence of L. plantarum Lp900, whereas this effect was not observed upon inulin supplementation of the low-calcium diet. Moreover, intestinal persistence of L. plantarum Lp900 was determined when provided as a probiotic (by itself) or as a synbiotic (i.e., in an inulin suspension) in rats that were fed unsupplemented diets containing the different calcium levels, revealing that the synbiotic administration increased bacterial survival and led to higher abundance of L. plantarum Lp900 in rats, particularly in a low-calcium-diet context. Our findings demonstrate that inulin supplementation can significantly enhance the intestinal delivery of L. plantarum Lp900 but that this effect strongly depends on calcium levels in the diet. IMPORTANCE Synbiotics combine probiotics with prebiotics to synergistically elicit a health benefit in the consumer. Previous studies have shown that prebiotics can selectively stimulate the growth in the intestine of specific bacterial strains. In synbiotic supplementations the prebiotics constituent could increase the intestinal persistence and survival of accompanying probiotic strain(s) and/or modulate the endogenous host microbiota to contribute to the synergistic enhancement of the health-promoting effects of the synbiotic constituents. Our study establishes a profound effect of dietary-calcium-dependent inulin supplementation on the intestinal persistence of inulin-utilizing L. plantarum Lp900 in rats. We also show that in rats on a low-dietary-calcium regime, the survival and intestinal abundance of L. plantarum Lp900 are significantly increased by administering it as an inulin-containing synbiotic. This study demonstrates that prebiotics can enhance the intestinal delivery of specific probiotics and that the prebiotic effect is profoundly influenced by the calcium content of the diet.